Summary of The "Carrefour de la Télésanté" 2014 which took place at la Cité des Sciences et de l'Industrie in PARIS on 16th and 17th October, 2014 - Pirkko Kouri (Finnish Journal of eHealth and eWelfare, 2014)
The conference was organised by ISfTeH (International Society of Telemedicine and eHealth, which mission is to facilitate the international dissemination of knowledge and experience in Telemedicine and eHealth and providing access to recognized experts in the field worldwide) and CATEL (which is a French association created in October 1997). CATEL has become a network of more than 20 000 actors concerned by telemedicine e.g. practitioners, firms, associations, institutions, labs.